Adapting legume crops to climate change using genomic approaches. - Mousavi-Derazmahalleh, M.; Bayer, P.; Hane, James; Babu, V.; Nguyen, H.; Nelson, M.; Erskine, W.; Varshney, R.; Papa, R.; Edwards, D. (Plant, Cell and Environment, 2018)
Our agricultural system and hence food security is threatened by combination of events, such as increasing population, the impacts of climate change, and the need to a more sustainable development. Evolutionary adaptation may help some species to overcome environmental changes through new selection pressures driven by cli- mate change. However, success of evolutionary adaptation is dependent on various factors, one of which is the extent of genetic variation available within species. Geno- mic approaches provide an exceptional opportunity to identify genetic variation that can be employed in crop improvement programs. In this review, we illustrate some of the routinely used genomics ‐ based methods as well as recent breakthroughs, which facilitate assessment of genetic variation and discovery of adaptive genes in legumes. Although additional information is needed, the current utility of selection tools indicate a robust ability to utilize existing variation among legumes to address the challenges of climate uncertainty.